IMPROVING MATHEMATIC CONNECTION AND COMMUNICATION CAPABILITY AND SELF-CONCEPT OF VOCATIONAL SCHOOL STUDENTS THROUGH THE SAINTIFIC APPROACH TO THE SETTINGS OF JIGSAW COOPERATIVE LEARNING MODELS - Herry Prasetyo ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2019)
This research was aimed at examining the improving mathematical connection and communication ability and self-concept of vocational students through cooperative learning of jigsaw so that they were able to be more motivated in learning mathematics, more understanding mathematics learning itself and to  apply it in everyday life. This research method was a quasi-pretest-posttest experiment that applied a jigsaw cooperative learning model. This study involved two groups of students who  studied about mathematical connection and communication skills and students' self-concepts. The instruments used were in the form of mathematical connection and communication skills, as well as student self-concept questionnaires. The research instruments were firstly tested for validity (logical and empirical), reliability, distinguishing features and the level of difficulty of the questions. The achievement of mathematical connections and communication skills and the self-concept of students who got learning with a scientific approach to the type of cooperative learning model jigsaw was better than students who only learned the scientific approach. In this study there was also an association between the ability of connections with mathematical communication of students in the high category. There was an association between the ability of connections with students' self-concepts in the high category. There was an association between mathematical communication skills and students' self-concepts in the high category.